2015
DOI: 10.1002/sm2.52
|View full text |Cite|
|
Sign up to set email alerts
|

Painful Intercourse Is Significantly Associated with Evoked Pain Perception and Cognitive Aspects of Pain in Women with Pelvic Pain

Abstract: IntroductionEvidence suggests that painful intercourse, pain-related psychosocial factors, and altered pain processing magnify the pain experience, but it is not clear how these factors are related to each other.AimThe aims were to (i) characterize differences between women with pelvic pain and pain-free women using a battery of pain-related psychosocial measures, clinical pain ratings, and evoked local and remote pain sensitivity; and (ii) examine the relationship between intercourse pain, clinical pain, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
0
13
1
Order By: Relevance
“…No differences in central pain gain (as the difference in pain ratings between the first few and the last few stimuli) 44 were observed between the study groups. Contrary to these findings, females with pelvic pain 80 , temporomandibular disorders 81 , and whiplash-associated disorders 82 show enhanced TSP to thermal or mechanical stimuli. Chua et al 83 observed conflicting responses in TSP after electrical stimuli in neck pain patients.…”
Section: Comparison Of Females With and Without Neck/shoulder Paincontrasting
confidence: 57%
“…No differences in central pain gain (as the difference in pain ratings between the first few and the last few stimuli) 44 were observed between the study groups. Contrary to these findings, females with pelvic pain 80 , temporomandibular disorders 81 , and whiplash-associated disorders 82 show enhanced TSP to thermal or mechanical stimuli. Chua et al 83 observed conflicting responses in TSP after electrical stimuli in neck pain patients.…”
Section: Comparison Of Females With and Without Neck/shoulder Paincontrasting
confidence: 57%
“…The most common side effects of LNG-IUS include amenorrhea, spotting and pelvic inflammatory disease. 10,11 Auhtors had 1 (0.58%) case of PID and LNG -IUS was removed in the second month of insertion. The levonorgestrel-releasing IUD has been successfully used in primary and secondary dysmenorrhea by suppressing endometrial prostaglandin synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that painful intercourse and pain-related psychosocial factors increase the pain experience, but it is unclear how these factors affect one another. Women with pelvic pain may perceive stimuli as more painful than pain-free women when the magnitude of the stimulus is the same [30]. A study of women with chronic pelvic pain found that these patients may show pain-related psychological behavior (including catastrophizing) and hypervigilance during intercourse.…”
Section: Discussionmentioning
confidence: 99%